Overcoming Classroom Silence - Tri Winindyasari Palupi; Yulieda Hermaniar (English Language Education Study Program of STKIP PGRI Banjarmasin, 2023)
Engagement is one of the essential aspects of having effective communication in English. In reality, English speakers, specifically language learners, often struggle and are unresponsive in communication, including in the classroom. This contradicts the purpose of learning that requires students and teachers to communicate effectively. In response to this issue, it is necessary to understand how teachers handle the problem through teaching strategies. This paper investigates teachers' strategies for engaging unresponsive students to teachers' questions. It is a qualitative study, with data collected through observations and interviews. The subject is an English teacher at SMKN 1 Tapin who taught tenth-grade students. The results show that the teacher used several strategies in engaging with unresponsive students, including humor, effective pacing, demonstrating intensity and enthusiasm, and pair work. Additionally, she also did code-mix with students' native language, constantly asking other students, and giving rewards. This proves the teacher's ability in exploring creative strategies to be engaging with her students.